The psychological skills of basketball athletes: Are there any differences based on the playing position? - Fitri Agung Nanda; Dimyati Dimyati (Program Studi Ilmu Keolahragaan Program Pascasarjana Universitas Negeri Yogyakarta, 2019)
Player-based psychological skills are an important factor that any coach should understand. Unfortunately, up to date there has not been any study that deals with the disclosure of player-based psychological skills especially for basketball athletes. Therefore, through the conduct of the study the researchers would like to identify the psychological skills of basketball athletes based on the playing position namely forward, guard and centre. The nature of the study is a quantitative-descriptive research with the retrospective causal-comparative design or ex-post factor design. Then, during the conduct of the study the researchers selected 24 basketball athletes who consisted of 11 forwards, 9 guards and 4 centres as the sample. In gathering the data, the instrument that had been implemented was the Psychological Skills Inventory for Sports (PSIS R-5). After the data had been gathered, the data were analysed by means of one way-ANOVA with the support from SPSS for the calculation. The results of the study show that there are significant differences on the psychological skills of the basketball athletes based on the playing position. Furthermore, it is also found that the basketball players who occupy the forward position has higher score of psychological skills in comparison to the basketball athletes who occupy the guard position and the centre position.